Etnozoologi Pada Masyarakat Sumba - Alda Rizkia Nikmatila; Insan Kurnia; Wulandari Dwi Utari (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
Ethnozoology is the study of the relationship between humans and animals. Ethnozoological studies are closely related to culture and local knowledge and their interactions with the surrounding environment. The Sumba people with the marapu belief are known to have close relationships with various types of animals. This study aims to identify the types of animals used by the people of three villages in Sumba. The results showed that 23 species of animals were identified as part of the ethnozoology of the three villages. Species of animals related to ethnozoology can refer to several species scientifically. The forms of utilization by the community are as part of traditional and religious rituals (five species), traditional medicine (five species), consumption (six species), artistic values ​​(seven species), and mystical values ​​and omens (seven species). Ethnozology in Sumba society is closely related to Marapu beliefs. Keywords: Etnozoology, Marapu, traditional rituals, Sumba